Effects of corrective and breathing exercises on respiratory function of older adults with a history of COVID-19 infection: a randomized controlled trial - Parisa Sedaghati; Korosh Fakhimi Derakhshan; Somayeh Ahmadabadi; Seyed Reza Rahimi Moghaddam (BMC, 2023)
Abstract Background Patients with a history of COVID-19 infection may suffer from different physical problems. This study aimed to investigate the effect of corrective and breathing exercises on improving respiratory function among patients with a history of COVID-19 infection. Methods In this clinical trial study, thirty elderlies with a history of COVID-19 disease were divided into two groups (mean age 63.60 ± 3.56 experimental, 59.87 ± 2.99 control groups) based on the study inclusion criteria. Exercise interventions included two sections- breathing exercises and corrective exercises in the cervical and thoracic spine. The spirometry test, craniovertebral angle, and thoracic kyphosis test were used. To evaluate differences between variables, paired-samples t-test and ANCOVA were used (p-value < 0.01). Also, Eta-squared was measured to assess the effect size. Results Results showed a significant difference between the two groups in craniovertebral angle (P = 0.001), thoracic kyphosis (P = 0.007), and respiratory capacity including Forced expiratory volume in one second (FEV1) (P = 0.002), FEV1/FVC (P = 0.003), Peripheral oxygen saturation (SPO2) (P = 0.001), while no significant differences were observed between two groups in terms of chest anthropometric indices (P > 0.01). The Eta-squared value of 0.51 for the Craniovertebral angle and the SPO2 indicates a large effect size. Conclusions The results showed the combination of corrective and breathing exercises could improve pulmonary function and correct cervical and thoracic posture in patients with a history of COVID-19 infection. Therefore, corrective and breathing exercises can be helpful as a complementary treatment along with pharmaceutical therapy to reduce chronic pulmonary complications in patients infected with COVID-19. Trial registration This research was registered in the Iranian Registry of Clinical Trials (IRCT registration number: IRCT20160815029373N7, First trial registration: 23/08/2021, Registration date: 01/09/2021).